Effect of substrate concentration on production of sorbitol - Nurhafizah, Abdul Malik (2014)
This research was conducted to study the effect of substrate concentration in production of sorbitol in fermentation process by Candida tropicalis (IFO 0618) that was purchased from America type Culture Collection (ATCC). The growth of the bacteria can be calculated using Monod Equation. Monod equation showed the relationship of specific growth rate to substrate concentration often assumes the form of saturation kinetics. Increasing in substrate concentration resulted in increasing the growth rate of the bacteria while changes in other nutrient was not affected the growth of the bacteria. In order to study the effective condition for the maximum growth of glucose, different substrate concentration of cellulose was used. Other parameter such as temperature, pH value, and time was constant. The pH 6 was maintained by sodium acetate buffer. This study was performed in 16 hours and the samples were collected every 2 hours to get their optimum density using UV- Vis Spectrophotometer. The commercial cellulose act as the food sourced for this research. YPD medium is the medium used for the growth and maintaining the cell of the Candida tropicalis . The medium was autoclaved before used for further process. In addition, all the preparation steps of bacteria and nutrient medium was done in laminar flow space to avoid any contamination. The production of sorbitol can be done by several steps; cultivation of yeast, inoculum preparation, solid state fermentation and lastly analysis. The analysis of sorbitol was done by determining the dry cell weight, determining kinetic parameter of the microorganism (Candida tropicalis) by Monod equation and HPLC analysis of the sorbitol. The highest substrate concentration showed the highest dry cell weight (g/L) obtained while there were low dry cell weight (g/L) obtained from the low of substrate concentration. The increasing of the dry cell weight showed that Candida tropicalis was able to react with cellulose to form sorbitol. Concentration of sorbitol was differing in every HPLC results as the substrate concentration was manipulated in this study